The State and the Citizen - Raciborski, Jacek (Journal of Public Governance, 2010)
The main point of the article is that the contemporary state is more powerful than ever in history, and that it derives its strength from its citizens’ high expectations regarding the quantity and quality of goods it provides. Despite many difficulties, states satisfy the needs of their citizens – it was particularly evident at the beginning of the economic crisis in 2008. However, the strength of the state is not balanced by active citizenship or a well developed civil society. The author exposes a twofold character of civil society whose citizens associate for fundamentally different reasons: a) to have an influence on the state’s actions and therefore to ensure its decisions are beneficial for them, b) to fulfill theirown needs through the association. In Poland, we can observe a serious deficit of citizenship both on an individual level and on the level of civil society in both its forms.